STIMULASI MOTORIK HALUS DAN BAHASA PADA ANAK USIA DINI DAYCARE X - Giovanni, Valencia; Christy, Secylia; Anindita, Nathania Etsa; Lofiandy, Licia Arista; Setiawan, Yuan Yovita (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
The high demands of modern life require parents today to work and adopt a dual-earner model, where both fathers and mothers are employed. As a result, some parents entrust their children to daycare centers. Daycare activities need to be carefully designed to align with and stimulate children's development according to their developmental milestones. This community service project focuses on assisting daycare centers in mapping children's needs and providing appropriate developmental stimulation. Assessments were conducted through interviews and observations, based on the Early Childhood Developmental Stimulation and Detection Standards (SDIDTK). A total of 9 children aged 24 to 48 months participated in the assessment. The results indicated that fine motor skills and language development still required stimulation. Some children still struggle to use their fingers and are not yet clear in pronouncing words appropriate for their age. Therefore, the researchers introduced targeted interventions, specifically finger-painting and sing-along activities. Following two intervention sessions, it was concluded that finger-painting and singing along could serve as effective developmental stimuli for children aged 24-48 months. However, the program's effectiveness could not yet be quantitatively evaluated. Nonetheless, caregivers reported positive outcomes, including improvements in children's language and fine motor skills, as well as increased engagement through more varied activities. Additionally, the group activities fostered children's social skills development. --- Tingginya tuntutan membuat orang tua pada masa kini perlu bekerja dan mengembangkan dual earner, yaitu kondisi Ayah dan Ibu sama-sama bekerja. Sebagian orang tua dengan tuntutan yang demikian pada akhirnya menitipkan anaknya di tempat penitipan anak atau daycare. Aktivitas daycare perlu dirancang untuk menyesuaikan dan menstimulasi perkembangan anak agar sesuai dengan milestone. Pengabdian kepada masyarakat ini berfokus untuk membantu daycare memetakan kebutuhan anak-anak dan memberikan stimulasi yang sesuai. Asesmen telah dilakukan dengan menggunakan wawancara dan observasi dengan mendasarkannya pada SDIDTK. Anak-anak yang terlibat dalam asesmen sebanyak 9 orang dan memiliki usia 24 hingga 48 bulan. Berdasarkan hasil asesmen, ditemukan bahwa perkembangan motorik halus dan bahasa anak masih perlu distimulasi. Oleh karena itu, penulis memberikan stimulasi yang dibutuhkan yaitu dengan program aktivitas finger-painting dan bernyanyi (sing along). Dari intervensi yang dilakukan sebanyak dua pertemuan, disimpulkan bahwa finger painting dan bernyanyi sing along dapat digunakan sebagai stimulasi tumbuh kembang anak usia 24-48 bulan. Meski demikian efektivitas program belum dapat dievaluasi secara kuantitatif. Namun, para pengasuh turut merasakan manfaat dari program ini, yaitu peningkatan kemampuan anak-anak khususnya dalam berbahasa dan motorik halus, serta adanya variasi kegiatan yang lebih menarik minat anak. Tak hanya itu, aktivitas yang dilakukan bersama-sama juga dapat menjadi stimulasi anak untuk mengembangkan keterampilan sosialnya.